2022
DOI: 10.1001/jamadermatol.2021.5119
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mortality Prognostication in Patients With Epidermal Necrolysis

Abstract: IMPORTANCEEpidermal necrolysis is a severe cutaneous adverse reaction in which severe systemic inflammation results in extensive epithelial keratinocyte necrosis. The most commonly used prognostic score in epidermal necrolysis, the Severity-of-Illness Score for Toxic Epidermal Necrolysis (SCORTEN), was recently found to overestimate mortality in contemporary cohorts. Identification of independent prognostic markers may help to stratify risk more accurately.OBJECTIVE This study evaluates the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
1
17
2
1
Order By: Relevance
“…In univariate analysis, it was associated with a higher risk of mortality (OR = 6.38 [CI 95%: 2.57-17.61], p = 0.00013), but not in multivariate analysis (OR = 2.16 [CI 95%:0.71-6.86], p = 0.18, Table 1). The results were similar with the threshold of 1.19 calculated by Koh et al 4 Neutrophils and NLR were not associated with mortality (p = 0.70 and 0.17, respectively). Conversely, the lymphocytes count, with a discriminant rate of 900/mm 3 , was associated with a higher mortality in univariate (p < 0.0001) and multivariate analysis (p = 0.0089, Table 1).…”
Section: Novel Inflammatory Markers and In-hospital Mortality In Epid...supporting
confidence: 91%
See 1 more Smart Citation
“…In univariate analysis, it was associated with a higher risk of mortality (OR = 6.38 [CI 95%: 2.57-17.61], p = 0.00013), but not in multivariate analysis (OR = 2.16 [CI 95%:0.71-6.86], p = 0.18, Table 1). The results were similar with the threshold of 1.19 calculated by Koh et al 4 Neutrophils and NLR were not associated with mortality (p = 0.70 and 0.17, respectively). Conversely, the lymphocytes count, with a discriminant rate of 900/mm 3 , was associated with a higher mortality in univariate (p < 0.0001) and multivariate analysis (p = 0.0089, Table 1).…”
Section: Novel Inflammatory Markers and In-hospital Mortality In Epid...supporting
confidence: 91%
“…2,3 Several studies suggested their association with the in-hospital mortality in EN. 4,5 We conducted a monocentric retrospective study to investigate the prognostic value of these parameters in our cohort of EN patients.…”
Section: Novel Inflammatory Markers and In-hospital Mortality In Epid...mentioning
confidence: 99%
“…Despite the high rates of cutaneous irAEs associated with ICI therapy, severe and lifethreatening skin reactions, such as TEN, were reported in approximately 2% to 3% of patients treated with a single-agent ICI. 3,4 In previous studies on TEN cases after the treatment by ICIs, patients were commonly treated by the high-dose corticosteroids or IVIG but with poor outcomes. We summarize these previously reported cases of ICI-induced TEN in Table 1.…”
mentioning
confidence: 99%
“…For example, iron metabolism and the capability of bone marrow to produce red blood cells may be affected by proinflammatory cytokines (interferon γ and tumor necrosis factor α), leading to an elevated RDW 20 . According to recent investigations, RHR is closely associated with SJS/TEN severity and can predict SJS/TEN mortality 21 …”
Section: Discussionmentioning
confidence: 99%
“…20 According to recent investigations, RHR is closely associated with SJS/TEN severity and can predict SJS/TEN mortality. 21 Serum albumin levels and total peripheral blood lymphocytes are used to calculate PNI, a commonly used indicator of nutritional status and inflammation. PNI is currently used for evaluating the immunonutritional status of patients with cancer and is a beneficial prognostic marker in adults with a variety of malignancies.…”
Section: Ta B L Ementioning
confidence: 99%